Foodborne illness among factory workers, Gweru, Zimbabwe, 2012: a retrospective cohort study. (December 2015) - Gabida, Meggie; Gombe, Notion; Chemhuru, Milton; Takundwa, Lucia; Bangure, Donewell; Tshimanga, Mufuta
Abstract Background On the 20th September 2012 the Gweru district medical officer (DMO) reported a sudden increase in the number of factory workers complaining of symptoms suggestive of gastrointestinal illness. We conducted a retrospective cohort study to determine factors associated with illness among factory workers. Methods A retrospective cohort study was conducted from September to October 2012 among 98 randomly selected factory workers. Interviewer administered questionnaires were used to evaluate possible risk factors from which food attack rates, relative risks (RR) and adjusted odds ratios (AOR) were calculated using Epi info version 3.5.1. Bacteriological examination of food samples was performed. In addition rectal swabs and specimens from food handlers and patients were collected for analysis. Results Of the 98 workers interviewed, 87/98 (89 %) were males. Consumption of beef stew (AOR = 9.28, 95 % CI 2.78–30.91) was independently associated with foodborne illness.Klebsiella spp. were isolated from beef stew and stool specimen of patients. Watery diarrhoea 51/98 (52 %), fatigue 48/98 (49 %) and abdominal cramps 41/98 (42 %) were the most presenting symptoms. Conclusions Klebsiella spp. was the aetiological agent for the food borne illness at the factory and this resulted from consumption of contaminated beef stew by the workers. As a result of this evidence, the implicated beef was withdrawn from the canteen and the menu cycle was revised to minimise exposure to the same food. Food handlers training in food safety and hygiene and regular canteen inspections for quality assurance were recommended and adopted. No further food borne illness has been reported from the factory.